Interfacial diffusion behaviour and mechanical properties of SiC/Ta hybrid accident tolerance fuel cladding structure. (February 2023) - Qin, Hailong; Li, Xiaoqiang; Zheng, Ce; Xu, Shanshan; Cheng, Laifei
Abstract: Innovatively designed CMCs/Ta/CMCs hybrid cladding tubes are promising accident-resistant fuel cladding materials, which are suitable for sodium-cooled fast reactors. In this work, such hybrid materials are designed and fabricated, the interfacial reaction mechanism between silicon carbide (SiC) and tantalum (Ta) are investigated after pressureless thermal treatment, and the mechanical properties of SiC/Ta joints are characterized at ambient temperature. A reaction zone with five distinct sublayers is formed in various annealing conditions. The reaction phases are identified using double CS-corrected STEM, and the diffusion path is experimentally validated as β-SiC | TaC | γ-Ta5 Si3 | α-Ta2 C | Ta2 Si | Ta3 Si | Ta. The mechanical properties of SiC/Ta samples are assessed by single-lap offset shear tests. In particular, the maximum shear strength of 13.86 ± 0.6 MPa is obtained after 5 h of annealing at 1500 °C. Four typical fracture models are established during the failure process.